2003
DOI: 10.1086/345498
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Fe ii Emission‐Line Strengths from Active Galactic Nuclei

Abstract: We present theoretical Fe II emission line strengths for physical conditions typical of Active Galactic Nuclei with Broad-Line Regions. The Fe II line strengths were computed with a precise treatment of radiative transfer using extensive and accurate atomic data from the Iron Project. Excitation mechanisms for the Fe II emission included continuum fluorescence, collisional excitation, self-fluorescence amoung the Fe II transitions, and fluorescent excitation by Ly α and Ly β. A large Fe II atomic model consist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
155
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(163 citation statements)
references
References 54 publications
7
155
1
Order By: Relevance
“…We modified the template following Kurk et al (2007) by adding a constant flux density between 2770 and 2820 Å equal to 20% of the mean flux density of the template between 2930 and 2970 Å. The justification for this operation comes from the theoretical Fe ii emission line strength of Sigut & Pradhan (2003). Since the Fe ii and the Mg ii are not distributed in the same way within the BLR, we decided not to fix the Doppler broadening of the Fe ii template to the one measured for the Mg ii emission line.…”
Section: Fe II Templatementioning
confidence: 99%
“…We modified the template following Kurk et al (2007) by adding a constant flux density between 2770 and 2820 Å equal to 20% of the mean flux density of the template between 2930 and 2970 Å. The justification for this operation comes from the theoretical Fe ii emission line strength of Sigut & Pradhan (2003). Since the Fe ii and the Mg ii are not distributed in the same way within the BLR, we decided not to fix the Doppler broadening of the Fe ii template to the one measured for the Mg ii emission line.…”
Section: Fe II Templatementioning
confidence: 99%
“…We took the relative strength of these lines from Korista (1992) (Korista 1992;Popović et al 2001Popović et al , 2002Popović et al , 2003. In comparison with the list of Fe II lines given by Sigut & Pradhan (2003), the Fe II template used here gives a better fit to the Fe II lines of the present sample of AGNs. (4) We included the He I λλ4921.93, 5015.68 Å lines (Véron et al 2002), assuming that they originate in the same region, i.e.…”
Section: Line Profile Analysismentioning
confidence: 99%
“…On the other hand, we include the He Iλ6678.15 Å and SiIIλ6371 lines (Véron et al 2002), and each line has been represented by one Gaussian. Also, one can expect a contribution of Fe II lines in the Hα wavelength region, but on the bases of the calculation given by Sigut & Pradhan (2003) In the fitting procedure we included these lines assuming that they originate from the same region, i.e. that they have the same width and redshift.…”
Section: Line Profile Analysismentioning
confidence: 99%
“…There are some indications that microturbulence may have a significant influence on the Fe II strength (Netzer & Wills 1983;Verner et al 2003;Sigut and Pradhan 2003;Baldwin et al 2004;Bruhweiler & Verner 2008;Sameshima et al 2011). Baldwin et al (2004) showed that a photoionization model may reproduce well the observed shape and the EW of the UV Fe II 2200-2800 bump, but only if a microturbulent gas motion is taken into account.…”
Section: Introductionmentioning
confidence: 99%